PERAN MEDIA MASSA DALAM PEMBINAAN KERUKUNAN HIDUP MAS YARAKAT DIKABUPATEN MAMUJU - Muhammad As'ad (Balai Penelitian dan Pengembangan Agama Makassar, 2007)
This research was conducted in Mamuju, West Sulawesi. Focus study isRadar Sulbar Newspaper and Radio Suara Manakarra. This researchaims to describe the role of mass media in socializing and constructingpluralism and multiculturalism. This use qualitative method where datawas collected by interview and article searching, and then analyzed bydescriptive analysis.This research indicates that the role of mass media in socializing andconstructing pluralism and multiculturalism is quite well. Process ofsocialization take place substantively. The program and rubric of thesemass media more for Islam people, as resident of majority, but it isn'tdiscriminative action.